Fear falls away and other essays from hard and rocky places - Bowers, Janice Emily (University of Arizona Press, 1997)
An avid hiker, backpacker, and lover of nature, Bowers shares her thoughts about some of her favorite mountains, canyons, and trails in southeastern Arizona's Santa Catalina Mountains as she contemplates moving away from the area.